1997
DOI: 10.4315/0362-028x-60.12.1560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acetic-Lactic Acid Treatments Applied to Beef Trim on Populations of Escherichia coli O157:H7 and Listeria monocytogenes in Ground Beef

Abstract: The efficacy of organic acid sprays for eliminating Escherichia coli O157:H7 and Listeria monocytogenes from beef trim used in a model ground beef production scheme was determined. Beef trim pieces with ca. 20% fat inoculated with E. coli O157:H7 or L. monocytogenes (ca. 3 log10 CFU/g) were utilized as controls or treated by spraying with 2 or 4% acetic and lactic acids. Propylene glycol (20%) was the carrier for each treatment. Following acid treatment, intact pieces were stored at 4°C for 12 or 24 h, ground,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…It is commonly known as vinegar which has antimicrobial capabilities due to its ability to lower the pH and cause instability of bacterial cell membranes [60] . Acetic acid has been shown to be effective against E. coli O157 H7, reducing this pathogens by 0.1 log 10 colony forming unit (cfu g −1 ) [61,62] . Also it reduced Salmonella typhimurium by 0.73 log cfu cm −2 on carcass tissue surfaces [63,64] but colour deterioration of whole muscle cut surfaces have been reported already [65] .…”
Section: Organic Acids As Preservatives To Prolong the Shelf Life Of mentioning
confidence: 99%
“…It is commonly known as vinegar which has antimicrobial capabilities due to its ability to lower the pH and cause instability of bacterial cell membranes [60] . Acetic acid has been shown to be effective against E. coli O157 H7, reducing this pathogens by 0.1 log 10 colony forming unit (cfu g −1 ) [61,62] . Also it reduced Salmonella typhimurium by 0.73 log cfu cm −2 on carcass tissue surfaces [63,64] but colour deterioration of whole muscle cut surfaces have been reported already [65] .…”
Section: Organic Acids As Preservatives To Prolong the Shelf Life Of mentioning
confidence: 99%
“…The authors reported that the use of 2 and 4% acid spray in beef trim stored at 4 °C reduced Listeria monocytogenes (initial concentrations 3 log 10 CFU/g) by 0.36 log 10 CFU/g and 0.44 log 10 CFU/g, respectively. The reduction in E. coli O157:H7 was lower than Listeria monocytogenes under similar conditions (Conner et al, 1997).…”
mentioning
confidence: 86%
“…The acid treatments for reducing E. coli O157:H7and Listeria monocytogenes levels in beef trim were found to be effective (Conner, Kotrola, Mikel, & Tamblyn, 1997). The authors reported that the use of 2 and 4% acid spray in beef trim stored at 4 °C reduced Listeria monocytogenes (initial concentrations 3 log 10 CFU/g) by 0.36 log 10 CFU/g and 0.44 log 10 CFU/g, respectively.…”
mentioning
confidence: 99%
“…However, there is a need to evaluate the potential for development of acid resistance in E. coli O157:H7 during application of acid decontamination interventions in meat (31). Studies have shown that the pathogen may survive decontamination of meat with lactic or acetic acid (7,16,17), suggesting that survivors can exist and may potentially adapt to the residual organic acid in situ in commercial meat processing environments (31).Berry and Cutter (6) demonstrated that previous acid adaptation of E. coli O157:H7 by culturing in media with 1% glucose (9) reduced the effectiveness of a 2% acetic acid solution to inactivate it on decontaminated beef. Recent studies from our laboratory have used meat decontamination runoff waste fluids of different pHs (acidic, acid-diluted, or nonacid-water spray washings) as a model system to evaluate responses of E. coli O157:H7 under conditions simulating those in meat plant environments (33,34,35,37,42).…”
mentioning
confidence: 99%
“…However, there is a need to evaluate the potential for development of acid resistance in E. coli O157:H7 during application of acid decontamination interventions in meat (31). Studies have shown that the pathogen may survive decontamination of meat with lactic or acetic acid (7,16,17), suggesting that survivors can exist and may potentially adapt to the residual organic acid in situ in commercial meat processing environments (31).…”
mentioning
confidence: 99%